The Impact of Oil Price Shocks on the Stock Markets of the G8 Countries - Shaeri, Komeil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
This study investigates the short term relationship between oil price shocks and real stock returns of the G8 countries over the period of 1993:1-2011:3. Empirical analysis shows that the stock markets of the net oil exporter members of the G8, have significantly and positively affected by different oil price shock specifications instantaneously or within one month. On the contrary, the net oil importer countries have shown negative responses to different oil price shocks. Another analysis revealed that oil price shocks contribute to the variation in real stock returns of the member countries but the magnitude of the contribution varies among them. Additionally, the impacts of positive and negative oil price shocks on real stock returns of these countries are not identical which verifies the asymmetric effect of oil price shocks. Also, the stock markets of the G8 countries are more affected by a U.S. real stock return shock than by an oil price shock. Thus, the existence of spillover effect from the U.S. stock market to the other stock markets has been validated. Keywords: Oil Price Shocks; Real Stock Returns; G8; VAR

ÖZ: Bu çalışma 1993:1 ile 2011:3 tarihleri arasında, G8 ülkeleri için, petrol fiyatlarındaki dalgalanmalar ile hisse senedi getirileri arasındaki kısa dönem ilişkiyi incelemektedir. Ampirik bulgulara gore, özellikle, net petrol ihracatcısı G8 ülkelerinde, hisse senedi piyasaları petrol fiyatlarındaki dalgalanmalardan, örneğin, 1 ay içerisinde olumlu yönde etkilenmektedir. Diğer taraftan, net petrol ithalatçısı ülkelerde ise, ilişkinin yönü negatif yöndedir. Diğer bulgular incelendiği zaman, petrol fiyatlarının, hisse senedi dalgalanmalarındaki varyasona da belirleyici olarak etki ettiği görülmektedir. G8 ülkeleri örneğinde, pozitif ve negatif etkilerin ayni seviyelerde olmadığı görülmektedir. Bu da bize petrol fiyatlarının asimetrik bir etkiye sahip olduğunu göstermektedir. Çalışmanın sonuçları ayni zamanda, G8 ülkelerindeki hisse senedi piyasalarının ABD’deki piyasalardan da etkilendiğini ortaya koymuştur. Anahtar Kelimeler: Petrol Fiyatı Şokları; Reel Hisse Senedi Getirileri; G8; VAR
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2013. Supervisor: Assoc. Prof. Dr. Salih Katırcıoğlu.
Keywords: Banking and Finance; Petroleum products - Prices; Petroleum industry and trade; Oil Price Shocks; Real Stock Returns; G8; VAR